E-STEM: Comparing Aggregator and Publisher E-Book Platforms. - Tara Tobin Cataldo; Michelle Leonard (Issues in Science and Technology Librarianship)
The University of Florida Libraries (UF), like many academic libraries, have been purchasing more e-books with each passing year. While most libraries that purchase e-books seemingly do so on very few platforms, the UF libraries currently have their collection of e-books available in over 35 different platforms. While this presents quite a challenge in terms of management it also presents an excellent opportunity for comparative analysis. Recent research focuses on the analysis of packages and the "big" deals, and highlights usage statistics but do not go into depth about the platforms and publishers. This article will compare Science, Technology, Engineering and Math (STEM) e-book platforms from both aggregators and publishers by examining features and usage statistics and making recommendations for consideration. [ABSTRACT FROM AUTHOR]